Hands-on web penetration testing with Metasploit : the subtle art of using Metasploit 5.0 for web application exploitation /: the subtle art of using Metasploit 5.0 for web application exploitation. (2020) - Singh, Harpreet; Sharma, Himanshu
No abstract available